(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The effects of chlorite on sandstone reservoirs have received more attention recently. Deeply buried sandstone reservoirs are prone to diagenetic alterations due to the presence of clays thereby affecting their reservoir quality (porosity). The effects of chlorite authigenesis on reservoir porosity are yet to be fully understood, and these create uncertainties in reservoir exploration of the fluvial reservoir in the basin. The Early Cretaceous Bima Sandstone which is divided into the Lower and Upper Members was deposited in a braided river to alluvial fan settings. An integrated approach, including thin-section petrography, Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD) analyses was employed in the study with the aim of determining the effects of different chlorite occurrences on reservoir quality (porosity). Sandstone reservoir quality depends on both depositional parameters like grain size, sorting and matrix content as well as diagenetic alterations. Chlorite formation involves the availability of precursor clays like smectite, kaolinite and berthierine as the material base and dissolution of detrital grains to provide Fe and Mg ions. Two types of authigenic chlorite occurrences were observed in this research; the grain-coating chlorite and the pore-filling chlorite. The study shows that chlorite sourced from smectite-dominant clays occurs as grain-coating thereby inhibiting quartz overgrowth, whereas chlorite formed from kaolinite are found as pore-fillings which leads to deterioration of reservoir porosity.